Management of Climatic Factors for Successful Silkworm (Bombyx mori L.) Crop and Higher Silk Production: A Review - V. K. Rahmathulla (Psyche: A Journal of Entomology)
The seasonal differences in the environmental components considerably affect the genotypic expression in the form of phenotypic output of silkworm crop such as cocoon weight, shell weight, and cocoon shell ratio. The variations in the environmental conditions day to day and season to season emphasize the need of management of temperature and relative humidity for sustainable cocoon production. The present review paper discuss in details about the role of temperature and humidity on growth and development of silkworm including recent studies on heat shock protein. Study also discusses the influence of air and light on silkworm development. In addition to this study emphasis on the role of various environmental factors on embryonic development of silkworm egg, nutritional indices of silkworm larva and reproductive potential of silkworm moth. The study also highlights about the care to be required during silkworm spinning and influence of temperature and humidity on post cocoon parameters of silkworm. The study included future strategies to be taken for the management climatic condition for successful cocoon crop. The paper covers 140 references connected with the topic.